2006
DOI: 10.1007/s00421-006-0154-4
|View full text |Cite
|
Sign up to set email alerts
|

PPARα gene variation and physical performance in Russian athletes

Abstract: Peroxisome proliferator-activated receptor alpha (PPARalpha) regulates genes responsible for skeletal and heart muscle fatty acid oxidation. Previous studies have shown that the PPARalpha intron 7 G/C polymorphism was associated with left ventricular growth in response to exercise. We speculated that GG homozygotes should be more prevalent within a group of endurance-oriented athletes, have normal fatty acid metabolism, and increased percentages of slow-twitch fibers. We have tested this hypothesis in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
4
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 18 publications
9
115
4
10
Order By: Relevance
“…We selected six polymorphisms in the PPARGC1A-NRF-TFAM pathway genes that are known to be associated with endurance exercise performance capacity: (i) NRF2 A/C (rs12594956) (Eynon et al 2009a); (ii) NRF2 A/G (rs7181866) (Eynon et al 2009d;He et al 2008); (iii) NRF2 C/T (rs8031031) (Eynon et al 2009a); (iv) peroxisome proliferator-activated receptor alpha (PPARA) intron 7 G/C (rs4253778) (Ahmetov et al 2006;Eynon et al 2009b); (v) PPARD C294T (Eynon et al 2009c;Skogsberg et al 2003);and (vi) PPARGC1A Gly482Ser (Eynon et al 2009c;Lucia et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…We selected six polymorphisms in the PPARGC1A-NRF-TFAM pathway genes that are known to be associated with endurance exercise performance capacity: (i) NRF2 A/C (rs12594956) (Eynon et al 2009a); (ii) NRF2 A/G (rs7181866) (Eynon et al 2009d;He et al 2008); (iii) NRF2 C/T (rs8031031) (Eynon et al 2009a); (iv) peroxisome proliferator-activated receptor alpha (PPARA) intron 7 G/C (rs4253778) (Ahmetov et al 2006;Eynon et al 2009b); (v) PPARD C294T (Eynon et al 2009c;Skogsberg et al 2003);and (vi) PPARGC1A Gly482Ser (Eynon et al 2009c;Lucia et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…The peroxisome proliferator-activated receptor α is a ligand-activated transcription factor which regulates expression of genes, involved in fatty acid uptake and oxidation, glucose and lipid metabolism [1,[20][21][22][23]. Endurance training increases the use of non-plasma fatty acids and may enhance skeletal muscle oxidative capacity through PPARA regulation of gene expression [21].…”
Section: Subjectsmentioning
confidence: 99%
“…Recently, it was demonstrated that the frequency of the PPARA rs4253778 GG genotype was significantly higher in Russian endurance-oriented athletes (Ahmetov et al, 2006), elite Israeli endurance athletes (Eynon et al, 2010), and elite Polish rowers than in controls or sprinters (Maciejewska, Sawczuk, & Cieszczyk, 2011). In accordance with the hypothesis that the observations of allele-frequency differences among athletes are mediated via fiber type, the mean percentage of Type I muscle fiber (determined by immunohistochemistry) was higher in GG homozygotes (55.5% ± 2.0%) than in CC genotype subjects (38.5% ± 2.3%) in a group of 40 physically active healthy men (Ahmetov et al, 2006).…”
Section: Peroxisome Proliferator-activated Receptormentioning
confidence: 99%